Physiotherapy Management In Reducing Hamstring Muscle Contracture Post Debridement: A Case Study - Nurul Fauziah Salsabila Putri; Muhammad Fashihullisan; Rakhmad Rosadi; Elsa Annisa Jannah (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Contracture is a shortening of the musculotendinous tissue that surrounds or is around a joint and creates significant resistance to passive or active stretching as well as limitations in the range of motion of the joint which can interfere with functional ability. This study aims to find out and explain the physiotherapy management in cases of hamstring muscle contracture et cause post surgical debridement. This research method uses a case study method with 1 respondent involved in this study. Providing interventions in the form of Ultrasound, Infrared, Electrical Stimulation, Hold Relax Stretching and ROM, strengthening exercises and Gait Training in 5 meetings during therapy. The research instruments used by researchers were Range of motion, Manual Muscle Testing, Barthel Index, Limb Length Examination, Upper Limb Segment Circumference, and Trendelenburg Test. As a result of providing physiotherapy intervention, the patient experienced an increase in ROM in knee extension and hip extension movements by 5° each.